Film Seeding for Bovine Myoblast Cell Optimization by Characterizing Growth - Isayiw, Luke. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Keyword: Agriculture engineering.